Sulek, Emilia Roza. 2019. Trading Caterpillar Fungus in Tibet: Book Review - Kukuczka, Anne (Swiss Journal of Sociocultural Anthropology, 2021)
Sulek, Emilia Roza. 2019. Trading Caterpillar Fungus in Tibet: When Economic Boom Hits Rural Area. Amsterdam: Amsterdam University Press. ISBN: 9789462985261. 328 p.